Rancang Bangun Sistem Pembacaan Jumlah Konsumsi Air Pelanggan PDAM Berbasis Mikrokontroler ATMEGA328 Dilengkapi SMS - Suardiana, I Made Nova; Agung, IGAP Raka; Rahardjo, Pratolo (Majalah Ilmiah Teknologi Elektro, 2016)
PDAM is still using analog flow meter. For PDAM customers, the information on analog flow meter are difficult to access and converted into payment amount. The system with analog read, PDAM officer was recorded by manual methods of data customer on the amount of water consumption. In this research using a water flow sensor YF-S201. Microcontroller ATmega328 receives the output pulses from the sensor. LCD is display information usage amount, time and date in real time. The module IComSat v1.1-SIM900 GSM / GPRS Shield SMS sending SMS based commands received from the customer and PDAM officer. The results achieved in this research is a sensor YF-S201 is able to read the amount of water consumed PDAM customers with an average deviation of 0.39%. The tests showed the result of conversion of payment are in accordance with the PDAM payment model in Gianyar district.
Keywords: PDAM; ATmega328; Sensor YF-S201; SMS